Science in Public: Communication, Culture and Credibility - Veronica Calderhead (Issues in Science and Technology Librarianship, 1998)
This article reviews the book Science in Public: Communication, Culture and Credibility. New York: Plenum Trade, 1998, by Jane Gregory and Steve Miller.